Resveratrol inhibits matrix metalloproteinases to attenuate neuronal damage in cerebral ischemia: A molecular docking study exploring possible neuroprotection - Pandey A.K.; Bhattacharya P.; Shukla S.C.; Paul S.; Patnaik R. (My University, 2025)
The main pathophysiology of cerebral ischemia is the structural alteration in the neurovascular unit, coinciding with neurovascular matrix degradation. Resveratrol has been reported to be one of the most potent chemopreventive agents that can inhibit cellular processes associated with ischemic stroke. Matrix metalloproteinases (MMPs) has been considered as a potential drug target for the treatment of cerebral ischemia. To explore this, we tried to investigate the interaction of resveratrol with MMPs through molecular docking studies. At 30 minutes before and 2 hours after cerebral ischemia/reperfusion induced by occlusion of the middle cerebral artery, 40 mg/kg resveratrol was intraperitoneally administered. After resveratrol administration, neurological function and brain edema were significantly alleviated, cerebral infarct volume was significantly reduced, and nitrite and malondialdehyde levels in the cortical and striatal regions were significantly decreased. The molecular docking study of resveratrol and MMPs revealed that resveratrol occupied the active site of MMP-2 and MMP-9. The binding energy of the complexes was –37.848672 kJ/mol and –36.6345 kJ/mol for MMP-2 and MMP-9, respectively. In case of MMP-2, Leu 164, Ala 165 and Thr 227 were engaged in H-Bonding with resveratrol and in case of MMP-9, H-bonding was found with Glu 402, Ala 417 and Arg 424 residues. These findings collectively reveal that resveratrol exhibits neuroprotective effects on cerebral ischemia through inhibiting MMP-2 and MMP-9 activity. © 2015, Editorial Board of Neural Regeneration Research. All rights reserved.